Design studio final product evaluation rubric in interior architecture education: Eskişehir Technical University case - Tuğba Levent Kasap; B. Burak Kaptan (IDA: International Design and Art Journal, 2022)
This study aims to develop an objective evaluation tool to evaluate final products in interior architecture design studios. Design studios generally apply personal evaluation methods or those predetermined by institutions to evaluate final products. However, such evaluations are often known to be far from being objective. In such evaluations, final product information might lead to a different value judgement that changes from person to person. Thus, a clear, accountable, fair, and objective evaluation tool developed according to this purpose might enable students and course instructors to evaluate themselves. In addition, subjective evaluations can be avoided. This study aims to develop a rubric to ensure an objective and fair evaluation of students’ products. Thus, the evaluation criteria used in this rubric were determined through the analysis of the data obtained from the forms sent to the instructors working in different universities and from the evaluation criteria used by the jury members. Under the light of these data, a new rubric was developed for each design studio group. Different jury members in different juries were asked to use two of these rubrics to provide some feedback about them.